Ice export from the Laptev and East Siberian Sea derived from δ18O values; Journal of Geophysical Research: Oceans; Vol. 120, iss. 9 - Rosen P.-O. Per-Olov; Andersson P. S.; Alling V. Vanja; Morth C.-M. Carl-Magnus; Bjork G. Goran; Semiletov I. P. Igor Petrovich; Porcelli D. Don (2015, 2015)
Title screen